Design and development of a computer program for the evaluation of the healthcare executive - biomed 2010. - Zotti, Daniel; Bava, Michele; Delendi, Mauro (Biomed Sci Instrum, 2010)
According to the Italian law which regulates executive healthcare contracts, the professional evaluation is mandatory. The goal of the periodic evaluation is to enhance and motivate the professional involved. In addition this process should 1. increase the sense of duty towards the patients, 2. become aware of ones own professional growth and aspirations and 3. enhance the awareness of the healthcare executive regarding the companys strategies. To satisfy these requirements a data sheet has been modeled for every evaluated subject, divided in two sections. In the first part, the chief executive officer (CEO) scores: 1. behavioral characteristics, 2. multidisciplinary collaboration and involvement, 3. organizational skills, 4. professional quality and training, 5. relationships with the citizens. The scores for these fields are decided by the CEO. In the second part the CEO evaluates: 1. quantitative job dimension, 2.technology innovation, 3. scientific and educational activities. The value scores of these fields are decided by the CEO together with the professional under evaluation. A previously established correction coefficient can be used for all the scores. This evaluation system model has been constructed according to the enhancement quality approaches (Deming cycle) and a web-based software has been developed on a Linux platform using LAMP technology and php programming techniques. The program replicates all the evaluation process creating different profiles of authentications and authorizations which can then give to the evaluator the possibility to make lists of the professionals to evaluate, to upload documents regarding their activities and goals, to receive individual documents in automatically generated folders, to change the correction coefficients, to obtain year by year the individual scores. The advantages of using this web-based software include easy data consultation and update, the implementation of IT security issues, the easy portability and scalability of the system itself in different contexts even beyond healthcare.